In-stent restenosis of superficial femoral artery: use all arrows in the quiver. Issue 10 (22nd October 2022) - Vadalà, Giuseppe; Ceresa, Fabrizio; Costa, Francesco; Bottari, Antonio; Roscitano, Giuseppe; Patanè, Francesco; Micari, Antonio
ABSTRACT: In-stent restenosis (ISR) is a common superficial femoral artery (SFA) stenting complication, occurring in more than one third of patients within 2–3 years after the index procedure. Moreover, there is no standard treatment for ISR, and although many options are available, there is still limited data regarding its optimal management. We report a paradigmatic case report of a patient complaining of symptomatic peripheral arterial disease, underwent multiple endovascular revascularizations for recurrent femoro-popliteal ISR. A step-by-step approach was followed. At the time of the first presentation, the ISR was treated by drug-eluting balloon (DEB) angioplasty. The repeated ISR was treated by laser debulking, achieving a good angiographic result. Finally, after the third repeated restenosis, a combined approach with laser debulking and DEB angioplasty guaranteed a good acute angiographic result. Long-term duplex-scan follow-up demonstrated the good patency of the femoro-popliteal target lesion.